Some properties of K-convex mappings in variable ordering settings. (9th December 2022) - Bouza Allende, Gemayqzel; Hernández Escobar, Daniel; Rückmann, Jan-J.
Abstract : We consider a generalization of standard vector optimization which is called vector optimization with variable ordering structures. The problem class under consideration is characterized by a point-dependent proper cone-valued mapping: here, the concept of K -convexity of the incorporated mapping plays an important role. We present and discuss several properties of this class such as the cone of separations and the minimal variable K -convexification. The latter one refers to a general approach for generating a variable ordering mapping for which a given mapping is K -convex. Finally, this approach is applied to a particular case.